A Retrospective Analysis of Patients' Conditions Using Acupuncture in a Traditional Korean Medicine Hospital. (1st October 2015) - Yun, Kyung-Jin; Lee, Ju Ah; Choi, Jiae; Ko, Mi Mi; Lee, Cham-kyul; Lee, Myeong Soo; Lee, Eun-Yong
Abstract : Objective. The aim of this study was to identify the patient demographics, health issues, and type of acupuncture treatments who visited a traditional Korean medical hospital for acupuncture treatment. Methods. We retrospectively analysed the data using the electronic medical records (EMRs) of patients treated with at least one treatment of acupuncture from 1 January 2010 to December 2012 in the Chung-Ju Korean hospital at Semyung University. Results. The total number of identified patients was 1189 inpatients and 10138 outpatients. The 50–59 age group received acupuncture treatment in the hospital the most, followed by the 40–49 age group. Among the patients undergoing acupuncture treatment because of a diagnosis of pain, 82.74% were outpatients and 72.85% were inpatients. Additionally, all patients with a spine condition received acupuncture treatment. The most common musculoskeletal conditions of patients at the traditional Korean medicine (TKM) hospital were associated with spine conditions, such as low back pain and neck pain. Various treatments have been performed at the hospital in conjunction with acupuncture. The study results show a high prevalence of acupuncture treatment for diagnosed diseases. Conclusion. Our study suggests the need to investigate additional TKM hospitals to analyse characteristics of patients who received specific treatments. Analysis of the characteristics of patients treated with Korean acupuncture at the TKM hospital in this study will help future researchers who want to implement strong clinical evidence. However, we cannot completely discount all symptoms because of the retrospective nature of this study, and only one hospital was used, which limits the generalisation of our findings.